Spiegare i passaggi.
Svolgere SENZA la tecnica X sostituzione.
Spiegare i passaggi.
Svolgere SENZA la tecnica X sostituzione.
Il prodotto suggerisce di risolverlo per parti.
per cui
$ = \frac{4}{5} x(x-1)^{\frac{5}{4}} - \frac{4}{5} \int (x-1)^{\frac{5}{4}} \, dx = $
$ = \frac{4}{5} x(x-1)^{\frac{5}{4}} - \frac{4}{5} \frac{4}{9} (x-1)^{\frac{9}{4}} +c = $
$ = \frac{4}{5} x(x-1)^{\frac{5}{4}} - \frac{16}{45} (x-1)^{\frac{9}{4}} + c = $
$ = \frac{4}{45} (9x-4x+4) \sqrt[4]{(x-1)^5} + c $
$ = \frac{4}{45} (5x+4) \sqrt[4]{(x-1)^5} + c $